The Importance of Engaging Children in Research Decision‐Making: A Preliminary Mixed‐Methods Study. Issue 3 (18th May 2020) - Paquette, Erin Talati; Palac, Hannah; Bair, Elizabeth; Schultz, Blake; Stenquist, Nicole; Joffe, Steven; Shukla, Avani
ABSTRACT: Studies demonstrate deficiencies in parents' and children's comprehension of research and lack of child engagement in research decision‐making. We conducted a cross‐sectional and interview‐based study of 31 parent‐child dyads to describe decision‐making preferences, experiences, and comprehension of parents and children participating in research. Parents and children reported that parents played a greater role in decisions about research participation than either parents or children preferred. The likelihood of child participation was associated with the extent of input the parent permitted the child to have in the decision‐making process, the child's comprehension, whether the study team asked the child about participation, whether the child read study‐related materials, the parent's marital status, and the child's race. Children had lower comprehension than adults. Comprehension was related to age, education, verbal intelligence, and reading of study‐related information. Parent understanding was associated with prospect for benefit and illness severity. Child participation may be improved by increasing parent‐child communication, emphasizing important relational roles between parent and child, respecting the developing autonomy of the child, increasing engagement with the study team, providing appropriate reading materials, and assessing comprehension.